Higher math skills: talented children and teenagers - Yucra Camposano, Jennifer (2017)
This article refers to talent: specifying definitions, explanatory models and identification of the same. Subsequently, it focuses on mathematical talent: how it is conceptualized, the usefulness of its identification in educational institutions, the importance of teachers’ knowledge of the diversity of students presented in the classroom, and then support creating an environment of true educational inclusion, considering the individuality of each student.